Fitness characteristics of youth silat performers / Mohammed Nizam Shafie - Shafie, Mohammed Nizam (Faculty of Sports Science and Recreation, 2014)
Silat is a popular Asian martial art. The primary purpose of this research was to profile the physiological characteristics of young silat athletes. Eight motor performance tests, including two newly developed silat-specific tests were administrated to a sample of 178 young exponents (96 males and 82 females) aged 13 to 16 years. Tests included squat, rebound and a threedirectional jump, handgrip strength, medicine ball throw, push-ups, yo-yo endurance and a 20's kick test. Overall results showed that male exponents outperformed the female exponents for most tests, the fitness of females did not change with age for any variable (all, p > 0.05), while males tended to improve their fitness with advancing age/maturation. The females were advanced, by about 2 years in the estimated age at peak height velocity (PHV) compared to the males (1.1 ± 0.7 versus -0.9 ± 1.1 y from PHV, p < 0.05). Measures of isometric strength (handgrip strength), upper body power (medicine ball throw) and endurance (push-ups), lower body power (squat-jumps), and endurance (yo-yo test) showed significant ( p < 0.05) gains after 15 year-old in boys. Novel data is presented that could be useful for benchmarking fitness in youth silat. Being involved in silat did allowed female exponents to maintain their fitness, whereas, male exponents improved their fitness at or post PHV. These gender-specific differences are attributed to differing maturational processes and the findings may be useful when devising training programmes to maximise fitness development in youth silat.